Analysis of synoptic conditions and storm waves events on Rio de Janeiro’s north shore - Amorim, Isadora Borges da Silva (2016)
This study is justified by the need to incorporate the analysis of atmospheric circulation conditions, in the synoptic scale, to studies of storm wave impacts on the coastline, using the support of knowledge already generated for the Campos Basin. In this sense, the objective is to identify and characterize the atmospheric synoptic conditions during events of stormy ocean waves in the Southwest Atlantic, especially those that reach the Rio de Janeiro`s coast, seeking to identify weather patterns during the generation, propagation and scattering of storm waves events, between 2004 and 2014. The methodological strategy was initially set the storm events in the period, which generated significant impacts on Rio de Janeiro`s coast, describing the conditions on which they occurred. For this task are used data compiled from Wave Watch III model. The next step was the description of the impacts on shoreline from the results of the simulations of shallow water wave propagation. The information from synoptic charts, published daily by the Brazilian Navy, during the approach of events, activity and dispersion of ocean storms that hit Rio de Janeiro coast later selected. Finally, they were described and mapped generating synoptic conditions of storm waves to the aforementioned coast. As a result it was found that the different paths patterns of low pressure centers vary between south towards north-east, Su-southwest to east-northeast and even Northwest to Southeast, the latter referring to a positioning of the closest to the coast cyclones Rio de Janeiro state. It was also inferred that the position and intensity of the vortex of high pressure in the South Atlantic (ASAS) interfere with the trajectories of low pressure centers. At the time of dissipation, the trajectories are from west to east. The November event 2008 is diagnostic of intense waves related to the position of the center of high pressure in the South Atlantic (ASAS).